Frataxin is localized to both the chloroplast and mitochondrion and is involved in chloroplast Fe-S protein function in Arabidopsis - Turowski, Valeria Rosana (2015)
Frataxin plays a key role in eukaryotic cellular iron metabolism, particularly in mitochondrial heme and iron-sulfur (Fe-S) cluster biosynthesis. However, its precise role has yet to be elucidated. In this work, we studied the subcellular localization of Arabidopsis frataxin, AtFH, using confocal microscopy, and found a novel dual localization for this protein. We demonstrate that plant frataxin is targeted to both the mitochondria and the chloroplast, where it may play a role in Fe-S cluster metabolism as suggested by functional studies on nitrite reductase (NIR) and ferredoxin (Fd), two Fe-S containing chloroplast proteins, in AtFH deficient plants. Our results indicate that frataxin deficiency alters the normal functioning of chloroplasts by affecting the levels of Fe, chlorophyll, and the photosynthetic electron transport chain in this organelle.